TINGKAT KEPUASAN â€œSANG PISANGâ€ DI KOTA MANADO - Cahyana ., Candova; Grace Adonia Josefina Rumagit; Leonardus Ricky Rengkung (Sam Ratulangi University, 2019)
The objective of this research is to determine the level of customer satisfaction â€œSang pisangâ€ toÂ products, the price of, place, promotion and services. This research is conducted from November to December2018. The data used in this study are primary data and secondary data. Primary data is obtained by directÂ interview to 44 respondents using questionnaires with Likert Scale. Respondent selection use accidentallysampling method. Secondary data obtained from local book stores and the internet through google scholar toÂ access articles from various scientific journals and thesis from other universities related to the topicÂ concerning the level of customer satisfaction. The research result showed that, the level of customerÂ satisfaction of â€œSang Pisangâ€ measured by product, price, place, promotion and service variables wasÂ 78.78%. Which is classified as satisfied. Satisfaction level of â€œSang Pisangâ€ Consumers are 80,79% ofÂ product and 80,18% of service. For the satisfied category, the price variable is 80.00%, the place is 76.27%,Â and the promotion is 75.68%.*jnkd+eprm*